Determinants of Economic Growth in Nepal: A Johansen Cointegration Analysis - Joshi, Uttam Lal (International Research Journal of MMC, 2022)
This research study investigates the determinants of Economic Growth in Nepal. GDP growth is the dependent variable and import, export, exchange rate, foreign exchange reserve, gross capital formation and broad money supply are the explanatory variables. Data since 1965 to 2020 are taken from secondary sources of World Bank to find the relationship between them. Augmented Dickey- Fuller Test is run to test stationary condition in the variables. Result of Johansen Cointegration Test supports the existence of cointegration in the model. The coefficient of VECM is negative and significant expresses the long run relationship and Granger Causality Test indicates the two way causality between LNFER and LNM2 with LNGDP and one way causality from LNIMP and LNEXR to LNGDP but inverse causality is seen from LNGDP to LNEXP. Results confirm the variables are the determinants of economic growth in Nepal. So policy makers should consider on these variables for economic growth of the country.